Factors Influencing Academic External Engagement, Global Mindedness And Internationalisation Satisfaction Among Academics In Malaysian Research Universities - Muthu, Kalanithi (2024)
The internationalisation of higher education is a crucial driver of national economic growth and global competitiveness. Malaysian research universities are increasingly focusing on enhancing their international profile and academic engagement. This study investigates the factors influencing academic external engagement, global mindedness, and internationalisation satisfaction among academics in Malaysian public research universities. Specifically, it examines the impact of perceived institutional support, technology integration, and talent management on global mindedness, and how these relationships are mediated by global mindedness and moderated by academic external engagement. Using Smart PLS to evaluate the hypotheses, the study found that perceived institutional support, technology integration, and talent management positively influence global mindedness among academics. Additionally, global mindedness significantly enhances internationalisation satisfaction. However, the study revealed that while academic external engagement strengthens the relationship between technology integration and global mindedness, it does not significantly moderate the relationships between institutional support or talent management and global mindedness.